Outpatient utilization patterns of the six main ATC drug groups in Republic of Croatia, City of Zagreb, and Croatia Counties in 2004 - Štimac Grbić, Danijela (Array, 2009)
Abstract: The aim of the study was to determine drug utilization according to Croatian counties, and to identify the causes of the possible between-county utilization variation. Zagreb Institute of Public Health in collaboration with the Croatian Drug Agency collected and analyzed data on outpatient utilization of the six main Anatomic-Therapeutic-Chemical (ATC) drug groups. Data on the number and size of packages, and on wholesale price were obtained from all pharmacies in Croatia. Based on these data, the number of defined daily doses (DDD) and DDD per 1000 inhabitants per day (DDD/ 1000/day) in 2004 were calculated for all drugs. County differences in the drugs utilization were calculated by use of relative standard deviation. This method revealed the outpatient drug utilization to vary among particular Croatian counties. Study results indicated the need of national guidelines for appropriate drug use to develop, along with education of the physicians and general population on their implementation